Adakah Perbedaan Faktor yang Mempengaruhi Tingkat Pengendalian Korupsi antara Negara Maju, Menengah dan Miskin? - Trijoko Prasetyo; Marselina Marselina (Jurnal Ekonomi Pembangunan, 2022)
The purpose of this study was to examine the effect of good government as measured by the level of democracy, the effectiveness of government and the quality of regulations on controlling corruption in high, midle and low income countries. Samples were high, midle and low income countries represented all continents in the world for 5 years. Research found that the level of democracy, government effectiveness and regulatory quality had a significant effect on the control of corruption, but the level of prosperity/economy income positively correlates with democracy, government effectiveness and regulatory quality so that countries with better income show higher variable levels both at the level of corruption control, the level of democracy, government effectiveness and the quality of regulation. Control of corruption in the High income countries just variable quality reguation is significant. In middle income countries level of democracy and government effectiveness that significant, and the low countries just only democracy that significant. These findings can be a policy in improving control of corruption depending ocountries income so that the policy can be more effective